Protective effect of aqueous extract, fractions and phenolic compounds of Hancornia speciosa fruits on the inflammatory damage in the lungs of mice induced by Tityus serrulatus envenomation. (June 2019) - Bitencourt, Mariana Angélica Oliveira; Torres-Rêgo, Manoela; de Souza Lima, Maíra Conceição Jerônimo; Furtado, Allanny Alves; de Azevedo, Eduardo Pereira; do Egito, Eryvaldo Sócrates Tabosa; da Silva-Júnior, Arnóbio Antônio; Zucolotto, Silvana Maria; Fernandes-Pedrosa, Matheus de Freitas
Abstract: Scorpion envenomation has been considered a public health issue around the world. Tityus serrulatus represents a specie of major medical importance in Brazil due to mortality rates of approximately 1% among children and elderly populations. The aim of this work was to evaluate the in vivo anti-inflammatory potential of aqueous extract from Hancornia speciosa fruits, its fractions and its phenolic compounds against T. serrulatus envenomation. After receiving the T. serrulatus venom (TsV, 0.8 mg/kg) intraperitoneally, the animals were treated intravenously with the aqueous extract (20, 30 and 40 mg/kg), the arachnid antivenom (50 μL/animal), the dichloromethane, ethyl acetate and n -butanol fractions (20 mg/kg) as well as rutin and chlorogenic acid (2, 2.5 and 5 mg/kg). The treatment with the aqueous extract, fractions and phenolic compounds decreased the migration of leukocytes to the peritoneal cavity and reduced the levels of IL-1β, IL-6 and IL-12. Moreover, the pulmonary histopathologic analysis showed a reduction in both interstitial and alveolar edema, as well as in the leukocytes infiltration and vascular ectasia in the mice's lungs, which evidences a protective effect attributed to H. speciosa . This is the first study that demonstrates the inhibitory potential of the aqueous extract from H. speciosa fruits against inflammation induced by TsV. These findings suggest that the bioactive compounds from the aqueous extract, especially chlorogenic acid and rutin, are responsible for the reported anti-inflammatory activity of H. speciosa . Graphical abstract: Image 1 Highlights: The aqueous extract from H. speciosa fruits inhibited leukocytes migration and levels of pro-inflammatory cytokines. The aqueous extract from H. speciosa fruits reduced edema, leukocytes infiltration and vascular ectasia in lungs. The H. speciosa fruits may have anti-inflammatory potential against Tityus serrulatus scorpion envenomation.